Teachers vs. the Uniqueness of Their Occupational Role. On the Need for Supervision in Educational Work - Żłobicki, Wiktor (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
The issues of the specificity of the teacher’s professional role and the various strategies for implementing this role are important issues of pedeutology. Often, the teacher’s role is unclear, internally incoherent, psychologically difficult and inconsistent with other important social roles to must carried out by a given person, which creates conditions conducive to professional burnout. One of the ways to prevent professional burnout is the possibility of a teacher using supervision, that is, using the consultation regarding their own professional work with a specialist supervisor. The purpose of such supervision may be not only the teacher’s relationship with the students, but in general the whole of teacher’s professional and personal development.
Keywords: teacher; professional role; prevent professional burnout; supervision